ANALISIS PEMIKIRAN IMAM AL-GHAZALI MENGENAI MEKANISME DAN ETIKA PERILAKU PASAR - Suprihatin Suprihatin; Ibdalsyah Ibdalsyah; Hendri Tanjung (Kasaba, 2019)
This research goal is to describe market based on Islamic and conventional economy from Imam Al-Ghazali. This reseach use qualitative approach. The findings are market and ethic operated by cognitive, affective dan skill. Imam Al-Ghazali has a concept about market mechanism based on Islamic law.